Invitation to sociology a humanistic perspective - Berger, Peter L. (Doubleday, a division of Bantam Doubleday Dell Publishing Group, Inc., 1963)
"This lucid and lively book, punctuated with witty, incisive examples, is addressed both to the layman who wants to know what sociology is all about -- and to students and sociologists who are concerned over the larger implications and dimensions of their discipline. The author views sociology in the humanist tradition and recognizes it as a 'peculiarly modern, peculiarly timely form of critical thought.' Without underestimating the importance of scientific procedures in sociology, he points out its essential affinity with history and philosophy, and he shows how sociology in this sense can contribute to a fuller awareness of the human world. 'Unlike puppets', he notes, 'we have the possibility of stopping in our movements, looking up and perceiving the machinery by which we have been moved. In this act lies the first step towards freedom.' Professor Berger discusses this consciousness in detail, in relation to one's own biography, to the operations of social institutions, and to the makeup of man as a product of these institutions. In each instance, he outlines the major contributions to sociology of such classical sociologists as Weber, Pareto, and Durkheim in Europe; Veblen, Cooley, and Mead in the United States; and some of the most important men in the field today."--Back cover.